2018
DOI: 10.1021/acs.est.8b00251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CO2 Phase States and Flow Rate on Salt Precipitation in Shale Caprocks—A Microfluidic Study

Abstract: Fracture networks inside the caprock for CO storage reservoirs may serve as leakage pathways. Fluid flow through fractured caprocks and bypass conduits, however, can be restrained or diminished by mineral precipitations. This study investigates precipitation of salt crystals in an artificial fracture network as a function of pressure-temperature conditions and CO phase states. The impact of CO flow rate on salt precipitation was also studied. The primary research objective was to examine whether salt precipita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 71 publications
3
54
0
Order By: Relevance
“…For decades, lab-on-chip experiments and micromodels have provided researchers in various research areas the opportunity to observe fluid flow and solute transport within the pore space (Karadimitriou and Hassanizadeh, 2012). However, majority of the microfluidic studies use engineered material, simple geometries, and ambient pressure-temperature conditions, which makes relevance and applicability of their results limited in the context of deep subsurface conditions in CCS and petroleum sectors (Porter et al, 2015;Nooraiepour et al, 2018b). In CCS, particularly, CO 2 is injected underground in supercritical state, which implies elevated pressure and temperature conditions.…”
Section: Description Of Experimental Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…For decades, lab-on-chip experiments and micromodels have provided researchers in various research areas the opportunity to observe fluid flow and solute transport within the pore space (Karadimitriou and Hassanizadeh, 2012). However, majority of the microfluidic studies use engineered material, simple geometries, and ambient pressure-temperature conditions, which makes relevance and applicability of their results limited in the context of deep subsurface conditions in CCS and petroleum sectors (Porter et al, 2015;Nooraiepour et al, 2018b). In CCS, particularly, CO 2 is injected underground in supercritical state, which implies elevated pressure and temperature conditions.…”
Section: Description Of Experimental Apparatusmentioning
confidence: 99%
“…We are making use of the HPHT microfluidic pressure vessel for a variety of research purposes. The first publication using the developed experimental setup and laboratory technique for sample preparation was on the physics of salt precipitation (Nooraiepour et al, 2018b). The second manuscript is in the final stage of preparation on the effect of mineral heterogeneity on geometry evolution and mineral dissolution in fractured carbonate-rich caprocks.…”
Section: Fabrication Of Microfluidic Specimensmentioning
confidence: 99%
“…More specifically, fractures serving as flow conduits may be clogged by the precipitating salts. Nooraiepour et al [97] studied how fractures in Draupne shale (primary caprocks for Smeaheia CO 2…”
Section: Dryingmentioning
confidence: 99%
“…Miri et al [92,93] demonstrated the importance of capillary forces on salt precipitation. It has been suggested that drying-induced salt precipitation may have fracture sealing potential [97]. However, it remains unknown whether salt precipitation has any effect on the mechanical properties of shale rocks close to fractures and to to what extent it influences fracture propagation.…”
Section: Dryingmentioning
confidence: 99%
“…(2) Validation with 4D Experiments. Challenges should also be focused on validation of numerical predictions [6] on pore-scale processes using wellcontrolled laboratory experiments [7,8]. It has been extremely difficult to visualize 3D time-series (i.e., 4D) data during laboratory experiments that investigate reactive transport through a porous and/or fractured medium at sufficient spatial and temporal resolutions, because the processes of interest occur (deep) inside the medium of interest.…”
Section: Next Challengesmentioning
confidence: 99%